Branching-Based Digital Fiction Storybook To Facilitate Elementary School Students' Reading Comprehension Learning - Ayu Safitri Syam; Wawan Krismanto; Muhammad Asrul Sultan (cendekia citra gemilang, 2026)
Students' reading comprehension remains suboptimal, so innovation is needed. The purpose of this study was to develop a branching-based digital fiction storybook to improve reading comprehension in elementary school students. This research was conducted using the ADDIE model, which included analysis, design, and development. The study was conducted with fifth-grade students at SD Negeri 85 Parepare. The subjects of this research included material experts, media experts, one class teacher, and fifth-grade students at the school. The resulting product is a digital book of branching fiction stories that can be accessed in portable document format or PDF. This product allows students to determine the storyline through the available choices. This product features colorful illustrations, story texts appropriate for elementary school students, and quiz activities developed with Wordwall and Google Forms to strengthen students' understanding of the reading content. The product developed has been deemed highly valid by both material and media experts. The practicality test of this product was deemed very practical by both teachers and students. Therefore, the branching model of digital fiction storybooks has been deemed worthy of development to facilitate reading comprehension in learning.